Performance in Contemporary Plastic Art ,as an Evolutionary Manifestation of Perspectival Representation - Mahood Mohammad, Zahraa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The research entitled (Performance as an Evolutionary Manifestation of Perspectival Representation) included Four chapters. The first chapter represented the Researc methodology , which contained the research problem, its importance, aims , Scope of the Study : spatial limits , Temporal Limits , and the definition of terms. The second chapter consisted of three sections. The first section dealt with linear perspective and the challenge of representing depth and spatial dimension. The second section addressed the shortcomings of geometric perspective representation and the foundations of the transition towards emotion as a gradual progression of performance. It also contained subheadings that included the intellectual and technical foundations of the perspective transition towards performance. One of them dealt with the change in the Trsnsformation of the human essence and its reflection in the formally formulated visible entities, while the other title highlighted the formative space as a modified perception site. As for the third section, it dealt with the partial manifestation of performance in modern arts such as Impressionism and Post-Impressionism, and later modern arts such as Abstraction, Cubism and Dadaism. Then it touched upon the explicit manifestation of the performance element in postmodern art as a tool and material structure for the artwork that possesses aesthetic values ​​different from traditional values, which we find in abstract expressionism and minimalist art. As a discourse aimed at achieving pragmatic Dispatch , as in event art, composition, and street art. The third include the Analysis of three Works .And the Fourth chapter addressed the research findings, which answered the research objectives by demonstrating how to justify the evolutionary consideration of perspective in its manifestations toward performance, followed by conclusions, recommendations, and suggestions DOI: https://doi.org/10.54633/2333-025-058-021